Experimental Study of a New Concrete Admixture and Its Function in Filling and Reinforcing Granite Fissures - Songnan Ru; Zuozhou Li; Handong Liu; Huaichang Yu; Chunlei Wei; Guangzhu Hu; Fangfang Xue; Congxian Wang; Jialiang Wang (Geofluids)
A concrete admixture with water retention and superhydrophobic properties was developed according to the high tensile strength, fissure resistance, and antiseepage requirements of concrete linings. Capillary water absorption, early-age anticracking, cube compressive strength, and splitting tensile tests were employed to study the effects of the new concrete admixture on the basic performance of concrete. On this basis, a triaxial compression test was conducted on granite fissures filled with concrete containing the admixture; the stress-strain and failure characteristics under different admixture dosages, confining pressures, and fracture widths were analyzed, and the reinforcement effect of the concrete with the admixture on the fractured rock mass was studied. The results show that the admixture can effectively improve the ability of concrete to resist water and fissures, and the concrete with the admixture significantly reinforced the fractured rock mass. Therefore, it can be widely applied in filling and reinforcing fractured rock masses.